2008
DOI: 10.1111/j.1523-536x.2008.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Caregivers of Very Low–Birthweight Infants

Abstract: Although very low-birthweight infants had poorer health and required significantly more health care resources than full-term infants, caregivers' quality of life did not differ between the two groups. Caregivers of both groups of infants reported substantial mental and physical health problems but perceived good quality of life. These data will aid parents, physicians, and policy makers as they struggle to make decisions concerning care of high-risk, costly, very low-birthweight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
(36 reference statements)
1
22
0
1
Order By: Relevance
“…Six studies were cross-sectional, two were case-control and four were longitudinal studies. Eight of the studies had at least one comparison group, such as caregivers and mothers of full-term infants [25][26][27], women with other pregnancy complication than a preterm delivery [28], mothers of nearterm (34-37 weeks of gestation) infants [27], parents of very low birth weight (VLBW) infants not participating in a Clinical Randomized Intervention Trial [30], mothers of preterm infants who did not require and previously received home oxygen therapy [31], mothers of infants who did not receive any intensive care or who received special care only for up to a maximum of 3 days [29] and families of neurologically normal infants [23]. The remaining four studies [32][33][34][35] assessed the QoL of mothers of preterm infants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies were cross-sectional, two were case-control and four were longitudinal studies. Eight of the studies had at least one comparison group, such as caregivers and mothers of full-term infants [25][26][27], women with other pregnancy complication than a preterm delivery [28], mothers of nearterm (34-37 weeks of gestation) infants [27], parents of very low birth weight (VLBW) infants not participating in a Clinical Randomized Intervention Trial [30], mothers of preterm infants who did not require and previously received home oxygen therapy [31], mothers of infants who did not receive any intensive care or who received special care only for up to a maximum of 3 days [29] and families of neurologically normal infants [23]. The remaining four studies [32][33][34][35] assessed the QoL of mothers of preterm infants.…”
Section: Methodsmentioning
confidence: 99%
“…In the total of the 12 papers, samples were composed mostly of mothers (n = 9), followed by samples of parents (n = 1), families (n = 1) and primary caregivers (n = 1). In the latter, 97.6% were mothers [25]. The gender of the participants is not specified in the study analysing families [23].…”
Section: Participants and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Eiser et al found that mothers of preterm infants at 2 years reported worse HRQoL than mothers of full-term infants [6], while another study found that HRQoL did not differ between caregivers of VLBW 1-year old infants and their counterparts. [7] These studies may be limited by the (1) focus on short-term HRQoL outcomes in parents; (2) use of convenience samples; and (3) lack of emphasis on a life-course perspective, thereby not controlling for important confounders. In addition, it has not been investigated what role stress may play in HRQoL of mothers of VLBW children.…”
Section: Introductionmentioning
confidence: 99%